Notch Signaling Pathway Is Involved in bFGF-Induced Corneal Lymphangiogenesis and Hemangiogenesis - Fang Xie; Xue Zhang; Wenting Luo; Hongyan Ge; Dawei Sun; Ping Liu (Journal of Ophthalmology)
Background. Notch/Dll4 involvement in cornea neovascularization (CRNV) and lymphangiogenesis is unclear. This study aimed to explore the role of notch signaling in basic fibroblast growth factor- (bFGF-) induced corneal lymphangiogenesis and hemangiogenesis. Methods. Corneal stroma of C57BL/6 mice was implanted with bFGF- or phosphate-buffered saline- (PBS-) soaked pellets. Corneal lymphangiogenesis and neovascularization were evaluated by immunofluorescence. Vascular endothelial growth factor-A (VEGF-A), Delta-like ligand 4 (Dll4), and Notch1 mRNA and protein expression were examined on days 1, 3, 7, and 14 by real-time polymerase chain reaction and western blot. Corneal cells were treated with ranibizumab, dexamethasone, and γ-secretase inhibitor (GSI). Microspheres were used to evaluate corneal hemangiogenesis in vivo. Results. Corneal hemangiogenesis reached its peak on day 7 after bFGF implantation, and corneal lymphangiogenesis was significantly higher on day 7 and 14, compared with PBS. mRNA and protein expression of VEGF-A, Dll4, and Notch1 were higher in bFGF-induced animal models compared with controls. Corneal hemangiogenesis and lymphangiogenesis decreased after 7 days of ranibizumab or dexamethasone treatment. After adding GSI for 24 h in bFGF-induced cells, the expression of Notch1 and Dll4 were downregulated compared with that in the control group whereas the expression level of VEGF-A was upregulated. Fluorescent particle number was higher in the GSI group. Ranibizumab and dexamethasone decreased the fluorescence signal. Conclusion. The notch signaling pathway plays a role in regulating VEGF expression, affecting corneal lymphangiogenesis and hemangiogenesis in mice. The molecular imaging probe technique can visualize the changes in the VEGF-A expression level of corneal limbus hemangiogenesis.